(Methanol-kappa O)(2-methyl-3-nitrobenzoato-kappa O)triphenyltin(IV) - Yip, F.W.; Teoh, S.G.; Yamin, B.M.; Ng, S.W. (International Union of Crystallography, 2010)
The five-coordinate Sn atom in the title compound, [Sn(C(6)H(5))(3)(C(8)H(6)NO(4))(CH(3)OH)], exists in a trans-C(3)SnO(2) trigonal-bipyramidal coordination polyhedron of which the O atoms of the methanol molecule and carboxylate group occupy the apical sites. In the crystal, adjacent molecules are linked by intermolecular O-H center dot center dot center dot O interactions, generating a helical hydrogen-bonded chain running along the b axis.